Symbols in the ritual of Rampanan Kapa' in Tana Toraja Regency: A study of semiotics - Palimbong, Daud Rodi; Maknun, Tadjuddin; Lukman, Lukman; Bandung, AB Takko (Edelweiss Applied Science and Technology, 2025)
The study researches the symbols in the Rampanan Kapa' ritual in Tana Toraja using the Roland Barthes semiotics approach. This ritual is part of Rambu Tuka', a thanksgiving ceremony that reflects the cultural values and social stratification of the Toraja people. By analyzing verbal and nonverbal symbols, this study uncovers the denotative, connotative, and mythical meanings in these rituals. This research is qualitative descriptive research that aims to study verbal and nonverbal symbols in the Rampanan Kapa' ceremony through a semiotic approach. The approach is used to understand ceremonies as a system of signs that contain cultural and social meaning. The data in this study were obtained from the Rampanan Kapa' ritual event using the total sampling technique due to the homogeneous nature of the data. Data collection is carried out through several methods, namely the listening method, recording technique, and documentation. The results of the study show that Rampanan Kapa', as part of the wedding tradition of the Toraja people, contains a rich and layered meaning. Denotatively, the symbols in this ceremony, such as betel nuts and beads, have a literal meaning as objects used in rituals. The betel serves as a sign of respect and agreement, while the beads symbolize the jewelry worn by the bride-to-be. At the connotation level, these symbols not only serve as physical objects but also represent social and cultural values, such as the beauty, glory, and dignity of a woman in Toraja society. Furthermore, the myths in Rampanan Kapa' explain the origins and spiritual meaning of the use of these symbols, reflecting the community's belief in the protection of ancestors as well as the importance of preserving traditions. By understanding these three layers of meaning, it can be concluded that Rampanan Kapa' is not only a wedding ritual but also a form of preservation of the identity and cultural heritage of the Toraja people.